2011
DOI: 10.4314/evj.v15i2.67691
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevalence of hydatidosis (<i>Echinococcus granulosus</i>, Batsch, 1786) in domestic animals in Ethiopia: A synthesis report of previous surveys

Abstract: Hydatidosis/echinococcosis (Echinococcus granulosus, Batsch, 1786) is considered to be a serious problem for both public health and the livestock economy in Ethiopia. The present paper reviews and summarizes available data on the disease. Abattoir survey data collected over a period of 15 years (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) were analyzed to assess the infection prevalence of hydatidosis in domestic animals in three different agroecological zones of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
2
29
2
Order By: Relevance
“…Seasonal variations in hydatidosis prevalence were also recorded through abattoir meat inspection [46], [47]. Other environmental factors found associated with CE in livestock were high altitudes and increasing annual rainfall [44], [48].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seasonal variations in hydatidosis prevalence were also recorded through abattoir meat inspection [46], [47]. Other environmental factors found associated with CE in livestock were high altitudes and increasing annual rainfall [44], [48].…”
Section: Resultsmentioning
confidence: 99%
“…Small ruminants have frequently been observed showing high rates of infection [47], [63], with sheep registering higher risk of infection compared to goats [51], [54], [57]. Cattle have also been identified in many studies as bearing the highest prevalence of CE of those observed in farm species [40], [44], [48], [64][66]. A study reported camels as the domestic intermediate host most likely to be infected, although cattle were recorded with the highest cyst intensity [47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of risk factors for intermediate host infection classified these broadly at the environmental, production system and animal level (Otero-Abad and . Most 'environmental factors' were due to spatial variation in the prevalence of infection (Ahmadi, 2005;Azlaf and Dakkak, 2006;Banks et al, 2006;Lahmar et al, 2007a;Acosta-Jamett et al, 2010b;Manfredi et al, 2013), although seasonal (AnsariLari, 2005;Daryani et al, 2007;Ibrahim, 2010), climatic (Acosta-Jamett et al, 2010b) and geographic (Fromsa and Jobre, 2011) effects have also been identified in some studies (although some of these conclusions are based on univariable analysis and therefore some apparent associations may be due to confounding). Extensive management systems have also been found to be associated with porcine CE infection (Sharma et al, 2004;Bruzinskaite et al, 2009).…”
Section: Risk Factors For Echinococcosis In Domestic Animalsmentioning
confidence: 99%
“…Echinococcus granulosus is highly prevalent in Ethiopia, and both sheep and goats commonly act as intermediate hosts (for a review see Kassa, 2012). Data from slaughterhouses in Robe, located approximately 30 km east of BMNP, suggest that the prevalence of E. granulosus in sheep is greater than 60% (Fromsa & Jobre, 2011). Local livestock herders commonly graze sheep and goats inside the BMNP (e.g.…”
Section: Discussionmentioning
confidence: 99%